Between Problem and Request: Are Students Ready to Accept Psychological Help - E. V. Nekhorosheva; D. A. Kasatkina (Moscow Polytechnic University, 2024)
University students demonstrate poor help-seeking behavior for their mental health and wellbeing despite frequently reporting low levels of wellbeing and psychological difficulties.The purpose of the study is to assess students' awareness of the possibilities of receiving help at the university; identify students' difficulties and support needs; spot preferred formats for receiving information about mental health, mental hygiene and well-being; and observe attitudes towards psychological support. The study of 654 students of Moscow City University was conducted as a sociological survey.Students experience the greatest need for support in situations of emotional and academic stress, and affective disorders. The preferred formats of assistance vary according to the type of student's needs, from acquiring self-care skills and managing emotions to advisory or therapeutic work. A special place is occupied by informing, education and non-specific social forms of support, in particular, environmental conditions and student communities. Students have ambivalent views and attitudes towards the supportive opportunities that the university provides them "here and now". Seeking help for students is associated with uncertainty and feelings of appropriateness, risk and mistrust, which can be levelled out in psychological education and training.